Does Sustainability Drive Loyalty: A Structural Equation Modeling of Tourist Behavior in Outdoor Recreation Destinations - Prawira, Aura Bulan Andhara; Pah, Jacob Ganef; Goeltom, Andar Danova L. (Journal of Consumer Studies and Applied Marketing, 2025)
This study investigates the structural mechanisms through which perceived sustainability influences tourist loyalty in the outdoor recreation sector. Drawing upon the Stimulus-Organism-Response (S-O-R) framework and the Natural-Resource-Based View (NRBV), a research model was developed to examine the sequential mediating roles of Experiential Value (EV), Destination Image (DI), and Tourist Satisfaction (TS) in the relationship between Perceived Destination Sustainability (PDS) and two distinct loyalty outcomes: Revisit Intention (RI) and Word-of-Mouth (WOM). Data were collected from 401 outdoor recreationists in Indonesia using a purposive sampling technique and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical results provide support for all eleven hypothesized relationships. The findings reveal that PDS serves as a potent primary catalyst, significantly enhancing EV and DI. Furthermore, the model demonstrates a robust sequential mediation chain, where sustainability perceptions translate into loyalty primarily by fostering mental restoration and personal growth (EV) and reinforcing a safe, credible brand image (DI). The model exhibits high explanatory power, accounting for 68.7% of the variance in Revisit Intention and 64.5% in Word-of-Mouth. Notably, the total indirect effect of sustainability on loyalty underscores that substantive sustainability practices are essential for long-term visitor advocacy. Theoretically, this research advances the S-O-R theory by validating a hierarchical "Organism" stage and decouples the satisfaction-loyalty link by showing a stronger propensity for digital advocacy over repetitive visitation among modern travelers. Managerially, the study suggests that destination operators should prioritize "experience curation" that facilitates mental renewal to bridge the gap between green branding and behavioral loyalty. Keywords: Sustainable Tourism, Outdoor Recreation, PLS-SEM, Experiential Value, S-O-R Framework, Tourist Loyalty, Indonesia.